OP62 How do Adiposity Trajectories Vary by Birth Cohort and Parental Social Class? Evidence from the West of Scotland Twenty-07 Study. (10th September 2013) - Shaw, R J; Green, M; Popham, F; Benzeval, M
Abstract : Background: Over the last 80 years the association between social class and obesity has changed. In the 1930s obesity rates were low and wealthy people tended to have a higher risk of obesity than poor people. However, rising affluence and industrialisation has lead to both rising rates of obesity and an obesogenic environment in which socioeconomically disadvantaged people have the highest risk of obesity. This study investigates the magnitude of these changes by modelling trajectories of adiposity by social class and cohort using the Twenty-07 study. Methods: The Twenty-07 study contains three cohorts of people (n = 4510), born in Glasgow in the 1930s, 1950s and 1970s. Two measures of adiposity, BMI and Waist to Height Ratio (WHtR), were recorded at baseline in 1987/8 when study participants were aged 15, 35 or 55, and again on 4 further occasions over 20 years. Parental social class (manual/non-manual) was collected at baseline. For each gender, we apply multilevel models to identify trajectories of adiposity by cohort and social class. Results: The trajectories indicated that adiposity increased with age and rates of increase varied by cohort, social class and gender. For any given age the youngest cohort had the fastest rate of increase and the highest predicted adiposity. For example, at age 35 for non-manual men, BMI was 24.2 (95% CI 23.7, 24.8) for the 1950s cohort and 27.2 (26.8, 27.5) for the 1970s cohort. By the end of the study respondents in more recent cohorts had BMI values approximately equivalent to those of people aged 20 years older in an earlier cohort. Cohort variation was much greater than socioeconomic variation. The smallest cohort difference in BMI was 2.10 (0.94, 3.26), a comparison of the 1950 and 1930s cohorts for non-manual men at age 55. In contrast, the largest social class difference in BMI, a comparison of manual and non manual women at age 64, was only 1.18 (0.37, 1.98). Socioeconomic inequalities tended to be smaller for men than women, particularly for the 1930s cohort where there was no evidence of a socioeconomic gradient for men unlike for women. The main difference between WHtR and BMI was that increases in WHtR accelerated with age whilst increases in BMI slowed with age. Conclusion: Increases in adiposity for younger cohorts across all socioeconomic groups dwarf any socioeconomic inequalities in adiposity. This highlights the damaging impact for the whole population of living in an obesogenic environment.